NuDURA press finish for viscose rayon and blended polyester: viscose rayon fabrics / Associate Prof. Salmiah Mohd. Nor, Associate Prof. Dr. Wan Yunus Wan Ahmad and Shamsu Bahari Abu Bakar - Mohd. Nor, Salmiah; Wan Ahmad, Wan Yunus; Abu Bakar, Shamsu Bahari (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2005)
A New Durable Press Finish, termed as NuDURA PRESS, with its formulation and application method was established for light and medium weight cotton and blended polyester/cotton fabrics. This NuDURA PRESS Finish was then applied on to light and medium weight viscose rayon and blended polyester / viscose rayon fabrics. The treated fabrics were tested and analyzed for their handle properties, abrasion resistance, strength, flame resistance, water resistance, colourfastness, dimensional stability and formaldehyde content. Overall, it was found that the handle properties, tearing strength, flame resistance, water resistance and dimensional stability of fabrics have improved. The colourfastness was maintained while the formaldehyde content of fabrics was acceptable. This NuDURA PRESS thus becomes a new finish for viscose rayon and blended polyester/viscose rayon fabrics. It has also become the ONE formulation and application method of the new Durable Press Finish, NuDURA PRESS for common cellulosic and blended cellulosic fabrics.